Epidemiologic, clinical, and economic profile of pediatric COVID-19 patients from an Indian context - Femida Rashid, Mansi Pawar, Jay Damani, Siddheesh Rajpurohit, Suneel Mundkur, Kanav Khera, Sreedharan Nair (Journal of Applied Pharmaceutical Science, 2024)
Coronavirus disease (COVID – 19 ) is known to be less severe in children, however, it has caused a great deal of anxiety among pediatricians. We aimed to understand and identify the potential risk factors, complications, and treatment contributing to COVID-19 in the pediatric population and to determine the direct cost burden. This study reviewed 176 patient medical records from January 2020 to August 2021 at two hospitals in coastal Karnataka. Patients younger than 18 years with a mean age of 5 (1-12) years, irrespective of gender were included. Patient information, such as demographics, medical history, and the direct cost of illness, was recorded in a pre-designed data collection form. Prior contact [60.23% (n, 106) ] and travel history [50% (n, 88) ] were the major risk factors. Respiratory distress syndrome [8.53% (n, 15) ] was reported as the most common complication, followed by seizures [6.82% (n, 12) ]. An association between seizures and Covid encephalitis was observed, where 1.7% (n, 3) of the male children who had seizures, developed COVID-19 encephalitis. Basic and advanced disease management programs are the main cost drivers. The direct medical cost analysis revealed a median cost of Indian rupees 25,813 (17,358- 42,320) [USD 312.81 (210.35-512.840) ] among the included patients. The current study recommends conducting future research to determine the total cost of illness, including both direct and indirect costs.
Keywords: Complications, COVID-19, direct cost, MISC, pediatrics